Atlas of atherosclerosis and metabolic syndrome - Grundy, Scott M. (Springer, 2011)
In this updated fifth edition of the Atlas of Atherosclerosis and Metabolic Syndrome (formerly the Atlas of Atherosclerosis), the editors have compiled a comprehensive update on the field of atherosclerosis. This four-color atlas includes detailed legends and extensive reference listings for hundreds of illustrations, algorithms, schematics, and images. This new edition focuses more closely on metabolic syndrome, as well as comprehensively covering many other topics including diabetes and vascular risk, obesity management, dietary concerns, drug treatment, gender and ethnicity differences, and many others. The striking, four-color format combined with the breadth of information it contains make this book an invaluable resource for physicians, cardiologists, and all professionals involved in the study and treatment of atherosclerosis.